Ecophysiology of amorphophallus eburneus Bogn - Jessie Blair, Garon. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The ecological study of A. eburneus was carried out at Gunung Rimau, Padawan. The total number of A. eburneus recorded was 239 plants with means of 48 plants per plot (20m x 20m). The ecological study revealed that 36 tree species was recorded from 208 trees with most dominant species were Diosyprus hermaproditica (IV = 45.56), followed by Grewia acuminata (IV = 27.59), Madhuca montleyana (IV = 23.47), Azadiractha excel/sa (IV = 21.86) and lastly by Scaphium sp. (I V = 17.30). Strong relationship in vegetative part of A. eburneus was recorded by the relationship between petiole height and petiole diameter with R2 = 0.9173 (y = 2.0333x + 21.997). In greenhouse study, A. eburneus grown under 75% shade level showed the highest development on petiole height, petiole diameter, number of leaflets and length of leatlets. For biomass allocation analysis, A. eburneus grown under 75% shade level also recorded the highest value of leaf area determination (LAD), while A. eburneus grown under 50% shade level recorded the highest value of dried mass production (OMP) and the highest value of net rate absorption (NAR) was recorded at 0% shade level.